2009
DOI: 10.21273/hortsci.19.2.340
|View full text |Cite
|
Sign up to set email alerts
|

Cowpeat as a Substitute for Peat in Container Substrates for Foliage Plant Propagation

Abstract: This study evaluated the potential for using cowpeat, a composted dairy manure, as a component of container substrates for foliage plant propagation. Using a commercial formulation (20% perlite and 20% vermiculite with 60% Canadian or Florida peat based on volume) as controls, peat was replaced by cowpeat at 10% increments up to 60%, which resulted in a total of 14 substrates. Physical and chemical properties such as air space, bulk density, container capacity, total porosity, pH, carbon-to-nitrogen ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 27 publications
(24 reference statements)
3
23
0
1
Order By: Relevance
“…Composted dairy manure solids were generated by Agrigy Co. (Clearwater, FL) at their Lake Okeechobee facility, where dairy manure solids were screened, composted in a large rotary drum composter at temperatures up to 65°C for 3 d, and allowed to cure in static piles (Nordstedt and Sowerby, 2003). Li et al (2009) reported a pH of 6.9, an EC of 4.8 dSÁm -1 , and a C:N ratio of 15.1 for composted dairy manure solids from the same source that were received at about the same time as our material. Vermiculite and perlite were purchased from Verlite Co. (Tampa, FL) and S&B Industrial Materials (Vero Beach, FL).…”
Section: Methodsmentioning
confidence: 68%
See 4 more Smart Citations
“…Composted dairy manure solids were generated by Agrigy Co. (Clearwater, FL) at their Lake Okeechobee facility, where dairy manure solids were screened, composted in a large rotary drum composter at temperatures up to 65°C for 3 d, and allowed to cure in static piles (Nordstedt and Sowerby, 2003). Li et al (2009) reported a pH of 6.9, an EC of 4.8 dSÁm -1 , and a C:N ratio of 15.1 for composted dairy manure solids from the same source that were received at about the same time as our material. Vermiculite and perlite were purchased from Verlite Co. (Tampa, FL) and S&B Industrial Materials (Vero Beach, FL).…”
Section: Methodsmentioning
confidence: 68%
“…Seven substrates were formulated by mixing Canadian sphagnum peat (S), Florida reed-sedge peat (R), and/or composted dairy manure solids (C) in the following ratios by volume: 1) 3S:0R:0C; 2) 0S:3R:0C; 3) 2S:0R:1C; 4) 0S:2R:1C; 5) 1S:0R:2C; 6) 0S:1R:2C; and 7) 0S:0R:3C, each with 20% vermiculite and 20% perlite. Canadian sphagnum peat was purchased from Fafard, Inc. (Apopka, FL); Li et al (2009) reported a pH of 3.9, an electrical conductivity (EC) of 0.32 dSÁm -1 , and a C:N ratio of 56.8 for Canadian sphagnum peat from the same source purchased at about the same time as our material. Florida reed-sedge peat was purchased from Reliable Peat Co. (Okahumpta, FL); Li et al (2009) reported a pH of 6.9, an EC of 0.31 dSÁm -1 , and a C:N ratio of 18.3 for Florida reed-sedge peat from the same source purchased at about the same time.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations